MANUSIA SEBAGAI HOMO ECONOMICUS: REFLEKSI ATAS KASUS-KASUS KEJAHATAN DI INDONESIA - Septiana Dwiputri Maharani (Jurnal Filsafat "WISDOM", 2016)
This research showed that First, ideally every man should act in a dual functions as individual beings as well as a social being. These dual functions of the real foundation for the building harmony in the life of a society. If lameness, especially the tendency of individuals includes positions as individual beings then building a life together can be as depicted in homo homini lupus, but building a harmonious society should be supported by common life, need, and give each other. Secondly, crimes in Indonesia are the fact how life in Indonesia has been overshadowed by very prominent self-interests. Personal interests which dominated by economic factors become a major influence in the crime trend. Indonesian human tendency their societies emphasize some aspects, but it turns out it's a proven fact that trend has begun to fade, although not all Indonesian people commit crimes. At least, homo economicus could be a tool to test the reality of Indonesian life. Third, Homo economicus is fully understood in an act that contradicts the notion homos socius. Homo economicus if not controlled will lead humanity in a situation of "war" as a Homo Homini Lupus.